2019
DOI: 10.1002/wer.1234
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification in a biofilm‐enhanced highly loaded aerated lagoon

Abstract: A full-scale biofilm-enhanced aerated lagoon using fixed submerged media was monitored using automated water quality monitoring stations over the span of one year to quantify its nitrification performance. The system was operating at a high organic loading rate averaging 5.8 g total CBOD 5 /m 2 of media per day (23.9 g total CBOD 5 /m 3 of lagoon per day), a total ammonia nitrogen loading rate averaging 0.9 g NH 4-N/m 2 day (3.7 g NH 4-N/m 3 day), and temperatures ranging from 1.6 to 20.8°C. The system showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In recent years, studies have outlined the use of rock or aggregate‐based attached growth systems (Mara & Johnson, 2006; Mattson et al, 2018; Swanson & Williamson, 1980), stationary in‐lagoon fixed‐film media (Gan & Champagne, 2015; Shin & Polprasert, 1988; Srinivas, 2007) and moving bed biofilm reactor (MBBR) systems (Delatolla et al, 2010; Hoang, 2013; Wessman & Johnson, 2006) to upgrade lagoons either by enhancing microbially mediated nitrification or by increasing the lagoon system’s volumetric or loading capacity. Numerous studies have recently demonstrated the effectiveness of nitrifying attached growth technologies, such as the MBBR to enhance TAN removal performance at the end of lagoons to meet stringent ammonia effluent guidelines at ultra‐low (0.6–3.0°C) temperatures (Ahmed et al, 2019; Almomani et al, 2014; Delatolla et al, 2010; Hoang, 2013; Patry et al, 2019; Young et al, 2016b). Post‐carbon nitrifying MBBR systems utilize plastic media with a high specific surface area to encourage the adhesion and attachment of nitrifying bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have outlined the use of rock or aggregate‐based attached growth systems (Mara & Johnson, 2006; Mattson et al, 2018; Swanson & Williamson, 1980), stationary in‐lagoon fixed‐film media (Gan & Champagne, 2015; Shin & Polprasert, 1988; Srinivas, 2007) and moving bed biofilm reactor (MBBR) systems (Delatolla et al, 2010; Hoang, 2013; Wessman & Johnson, 2006) to upgrade lagoons either by enhancing microbially mediated nitrification or by increasing the lagoon system’s volumetric or loading capacity. Numerous studies have recently demonstrated the effectiveness of nitrifying attached growth technologies, such as the MBBR to enhance TAN removal performance at the end of lagoons to meet stringent ammonia effluent guidelines at ultra‐low (0.6–3.0°C) temperatures (Ahmed et al, 2019; Almomani et al, 2014; Delatolla et al, 2010; Hoang, 2013; Patry et al, 2019; Young et al, 2016b). Post‐carbon nitrifying MBBR systems utilize plastic media with a high specific surface area to encourage the adhesion and attachment of nitrifying bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have outlined the use of rock or aggregate-based attached growth systems (Swanson and Williamson, 1980;Mara and Johnson, 2006;Mattson et al, 2018), stationary in-lagoon fixed film media (Shin and Polprasert, 1988;Srinivas, 2007;Gan and Champagne, 2015) and MBBR systems (Wessman and Johnson, 2006;Delatolla et al, 2010;Hoang, 2013) to upgrade lagoons either by enhancing microbially-mediated nitrification or by increasing the lagoon system's volumetric or loading capacity. Numerous studies have recently demonstrated the effectiveness of attached growth nitrification systems to enhance TAN-removal performance in lagoons to meet stringent ammonia effluent guidelines at ultra-low (0.6 -3.0°C) temperatures (Delatolla et al, 2010;Hoang, 2013;Almomani et al, 2014;Young et al, 2016b;Ahmed et al, 2019;Patry et al, 2019). However, a fundamental lack of knowledge remains regarding the capacity of attached growth systems to perform total nitrogen removal (nitrification and denitrification) in municipal lagoon effluents at ultra-low temperatures (0.6 -3.0°C).…”
Section: Introductionmentioning
confidence: 99%